Analisis Aplikasi Iuran Pengelolaan Lingkungan Berbasis Web Dengan Proses Monitoring dan Evaluasi COBIT 4.1 (Studi Kasus Perumahan Metro Residence) - Edlianto, Dionisius Riyan; Susanto, Agung Budi; Tukiyat (Jurnal Ilmu Komputer, 2024)
Metro Residence Housing has a total of 381 houses. The sales admin manually inputs environmental management contribution data into Excel every month. To address this, an application was created using the Scrum method, chosen for its adaptability and efficiency. Sprints one to three, each lasting two weeks, completed in six weeks. Post-development, a black box test with eight menu tests confirmed the system's functionality, with all tests passed. Subsequent direct testing with the admin over a month led to application acceptance. An IT governance audit followed, involving five respondents: sales admin, estate admin, admin manager, branch IT staff, and HO IT staff. The COBIT 4.1 audit rated Bogor Metro Residence at level three, indicating standardized, documented, and communicated IT procedures. Limited IT staff understanding prevented a higher score. The application can be further developed into a mobile app for residents to monitor bills and make payments.